DABCO‐modified super‐paramagnetic nanoparticles as an efficient and water‐compatible catalyst for the synthesis of pyrano[3, 2‐c:5, 6‐c']dichromene‐6, 8‐dione derivatives under mild reaction conditions. (7th October 2018) - Heydari, Zahra; Bahadorikhalili, Saeed; Ranjbar, Parviz Rashidi; Mahdavi, Mohammad
Abstract : In this paper, a novel catalyst is introduced based on the immobilization of 1, 4‐diazabicyclo[2.2.2] octane (DABCO) on super‐paramagnetic iron oxide nanoparticles. For the synthesis of the catalyst, silica‐magnetic iron oxide core‐shell nanoparticles were first functionalized by (3‐chloropropyl)trimethoxysilane. The functionalized silica‐magnetic iron oxide core‐shell nanoparticles then reacted with DABCO to form the final catalyst. The catalyst was characterized by scanning electron microscopy, vibrating‐sample magnetometer, thermogravimetric analysis, X‐ray photoelectron spectroscopy and Fourier‐transform infrared spectroscopy. This catalyst was used for the synthesis of pyrano[3, 2‐ c :5, 6‐ c ']dichromene‐6, 8‐dione derivatives. Several starting materials were used, and all of them led to the desired products in high isolated yields (19 examples). The catalyst also showed very good reusability in the reaction. Abstract : A novel catalyst is introduced based on the immobilization of DABCO on magnetic nanoparticles. The catalyst is characterized by various methods, including SEM, VSM, TGA and FT‐IR spectroscopy. This catalyst is used for the synthesis of pyrano[3, 2‐ c :5, 6‐ c ']dichromene‐6, 8‐dione derivatives. Several starting materials containing electron‐donating or electron‐withdrawing functionalities were used, and all of them led to the desired products in high isolated yields (19 examples). The catalyst also showed very good reusability in the reaction.